Development of Innovative Teaching Materials through Scientific Approach - Suarman Suarman; Hendripides Hendripides; Nurul Hikmah (Universitas Riau, 2018)
This study aims to develop teaching materials of economic learning assessment through scientific approach. The research used Research and Development (R&D) method that developed by Thiagarajan, Semmel, and Semmel that includes defining phase, design stage, and development stage. Data were collected from the assessment of three experts through an expert validation sheet and responses from 40 students through student response questionnaire. Data analysis using quantitative descriptive technique. The result of the research showed that the teaching materials are suitable for learning through the scientific approach on the course of the Economic Learning Assessment. of material experts with an average score of 89.47% (very good) and student response results with an average score of 86.45% (very good). Some suggestions from the experts include in the teaching material description section added with illustrations in the form of drawings or schemes; and equipped with concrete examples in accordance with the contextual situation. While the suggestions from the students are also in line with the advice of the expert team that is also equipped with concrete examples to be more reproduced.